The Urgency of Health Insurance Systems as Safety Education Efforts for Informal Sector Workers in Garage - Izyati, N. Jamilatul; A, Irman Syahrul; A, Nadya Aulia; H, Rizki Amelia; I, Devina Aura; D., Alicia Rosalinda (Universitas Negeri Semarang, 2023)
The informal sector needs to be officially registered or officially recognized by the government and often involves unstable work and lack of access to social security, including occupational health insurance. In the informal sector, work is usually done without formal employment contracts, and wages are uncertain, resulting in economic instability and uncertainty for workers. Workshops are one of the most common informal sectors in Indonesia. Workers in the informal sector, such as workshops, also have the same risks as formal workers, such as the risk of workplace accidents and illnesses that can affect their well-being and productivity. This study used a qualitative descriptive research method. This data collection technique was a field study with direct observation using interview research instruments. Based on the results of interviews and direct observations, workers at custom Garage did not have employment guarantees. The company also needed to include its workers in Badan Penyelenggara Jamunan Sosial Ketenagakerjaan.